Effect of irradiation time in the synthesis of Au-Ag nanoalloys by femtosecond laser. (August 2019) - Hidayah, A N; Triyono, D; Herbani, Y; Isnaeni,; Suliyanti, M M
Abstract: The synthesis of metallic nanoparticles can be performed by femtosecond laser-induced photoreduction of the metallic ion solution. Due to hydrogen radical and the solvated electron generated through the interaction of ultrafast laser and water medium, the dissolved metallic ion in the medium can be converted to their respective metallic atom and then precipitated into nanoparticles. When there is more than one metallic ion available in the solution, alloy nanoparticles can be generated. One parameter that affects this laser-based synthesis was the duration of laser irradiation time that has an advantage for size modification of nanoparticles. In this work, we have synthesized Au-Ag nanoalloys from the mixture of Au and Ag ion in various volume fraction in water medium added with 0.01wt% polyvinylpyrrolidone (PVP) as a capping agent and irradiated for 5 and 10 minutes. The result showed that there was linear shifting in surface plasmon resonance (SPR) of the nanoalloys in respect with their volume fraction of the ions. The results also revealed that the nanoparticle size was indeed reduced as the laser irradiation was prolonged, i.e., Au50Ag50 has a particle size of 7.98 nm and 5.18 nm for 5 and 10 minutes irradiation time, respectively.